Dollar a Day Re-Revisited - Friederike Greb; Stephan Klasen; Syamsul Hidayat Pasaribu; Manuel Wiesenfarth (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2011)
Recently, the World Bank re-estimated the international poverty line used for global poverty measurement and the first Millennium Development Goal based on an updated country sample of national poverty lines and new results for PPP exchange rates. This generated the new international poverty line of 1.25 per capita per day in 2005PPP. In this paper we show, using the same data, that the best statistical estimation of the relationship between mean consumption and national poverty lines generates an international poverty line that is substantially higher than 1.25 a day.
Keywords: 330